Peningkatan Kemampuan Berhitung Anak dengan Puppet Fun di Taman Kanak-kanak - Medayanti, Eli; Saridewi, Saridewi (Penerbit Aksara Rentaka Siar (ARS), 2019)
The background of the study is that children still do not know the symbol of numbers especially 1-20. The ability of children to count the number of objects, connecting with numbers and in sorting numbers is still low. The purpose of this study is to improve children's numeracy through fun puppet media. This type of research is classroom action research (CAR). The research subjects for the B1 early childhood group numbered 15 children consisting of 8 boys and 7 girls. This research was conducted in two cycles, each cycle of three meetings. The technique used in data collection is observation and documentation and the assessment results are processed by percentage techniques. The results showed that in the first cycle the effect of increasing the numeracy ability of children through fun puppet media developed according to expectations (BSH), the average percentage had not reached the KKM, the study was continued to cycle II. In the second cycle, there was an increase in the numeracy skills of children through very well developed puppet media (BSB) which had reached KKM. It can be concluded that puppet fun media can improve the numeracy skills of B1 group children in Fadhilah Amal 3 Kindergarten Tunggul Hitam Padang.